Rotational angiography and the contribution of roadmapping to the occlusion of arteriovenous malformations. Case resolution - Domingo López Vázquez (REC: Interventional Cardiology (English Ed.), 2022)
CASE RESOLUTION The procedure was performed under general anesthesia and with the administration of the standard dose of sodium heparin to prevent thrombosis or systemic embolisms (high risk considering the patient’s condition) via venous femoral access. This procedure was planned using 3D reconstruction through rotational angiography (figure 1 and video 1 of the supplementyary data). Embolization was guided using the roadmapping technique that merges the 3D reconstruction simultaneously while overlapped to the 2D reconstruction in the x-ray image projection required during multiple occlusion device implantations. Figure 1. 3D reconstruction of a pulmonary arteriovenous malformation from data obtained from the rotational angiography performed. The medical equipment used during the procedure included 4-Fr guide-catheters (using JR4 or MP catheters based on the anatomical needs of each patient), coils (Concerto Coil System 5/20 mm; Medtronic, United States), and vascular occluder devices (4 mm to 8 mm Amplatzer Vascular Plug from; Abbott, United States). A staged occlusion strategy was planned that started with the peripheral closure of the arteriovenous malformations (AVMs) using coils followed by the closure of nutrient vessels with coils and vascular plugs. Indeed, according to former studies, both devices combined are associated with a low rate of recanalization after embolization.1 This is the approach that...